The Role of Customer Satisfaction in Mediating the Effects of Product Quality and Service Quality on Repurchase Intention: A Study at Mr. Konveksi Bali - Ni Ketut Gustini; Ni Nyoman Kerti Yasa; I Gusti Ayu Ketut Giantari; Ni Made Asti Aksari (Asian Journal of Management Analytics, 2026)
This research examines the role of customer satisfaction as an intervening variable connecting product and service quality with customers’ intention to repurchase in the MSME context. Despite increasing competition in the post-pandemic period, maintaining customer loyalty remains a critical challenge for small businesses. A quantitative research design was implemented using survey data gathered from 120 participants who had prior purchasing experience. The study employed PLS-SEM to assess the relationships among variables, including both direct and indirect effects. The analysis indicates that both product and service quality have a significant effect on customers’ intention to repurchase. These results highlight the importance of delivering consistent service interactions alongside reliable product performance. From a managerial perspective, MSMEs should prioritize customer-centric strategies that enhance experiential value to sustain long-term purchasing behavior.